Diagnostic approach and clinical management in collodion babies: A case report - Setiowati, Ariani; Ayuningtyas, Wurry; Handayani, Kartika Darma; Angelika, Dina; Etika, Risa; Utomo, Martono Tri (Edelweiss Applied Science and Technology, 2025)
Collodion baby (CB) is a rare form of congenital ichthyosis, characterized by hyperkeratosis, severe erythroderma, and minimal desquamation. It is a rare condition with a prevalence of one in 300,000 live births and is usually born prematurely. The baby’s thick, shiny crust can cause eyelid ectropion, lip deformation, underdeveloped cartilages, and affect the newborn’s lung functions, leading to dehydration, malnutrition, hypoxia, and lung infections. The success of the diagnostic approach and clinical management in collodion baby is reported. A 15-hour-old baby girl, J, was born at Fatimah Probolinggo Hospital on July 29, 2024, with tense and blistered skin since birth. She was the second child born by cesarean section with a history of maternal labor. The baby received Vitamin K and Hepatitis B injections shortly after birth. The parents reported a similar complaint in their first child, a collodion baby. After physical examination, laboratory tests, and echocardiography, J was diagnosed with lamellar ichthyosis and ocular ectropion. An echocardiogram was performed on August 2, 2024, and the diagnosis was suspected as collodion syndrome accompanied by extropion oculo dextra sinistra and lamellar ichthyosis. On August 7, 2024, J experienced significant improvement and was discharged from the hospital. A comprehensive approach and treatment from a combination of specialties can improve the prognosis of infants with collodion.